Evaluating the theory of constraints business strategy approach from the perspective of the schools of strategic thought - Soares, Themer Miralha [UNESP]; de Souza, Fernando Bernardi [UNESP]; Cottas, Carlos Roberto Garcia [UNESP] (My University, 2023)
The theory of constraints (TOC) has long been developing methods to assist the strategic planning processes of organisations. However, such methods have received little academic attention. The objective of this article, by way of a systematic literature review, is to identify the main points of strategic planning from a TOC perspective and then compare them with the ten schools of strategic thought identified within the literature. The study reveals that TOC presents parallels with the premises of a number of these schools of thought, but it also posits particularities in regard to its own proposals for formulating and executing business strategies.
Keywords: business strategy; schools of thought; strategic planning; strategies and tactics tree; theory of constraints; TOC; viable vision